2022
DOI: 10.1021/acs.energyfuels.2c01522
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Spectral Correction in Fluorescence Spectroscopic Studies of Crude Oils and Asphaltenes

Abstract: Fluorescence spectroscopy has been widely used in biochemistry to elucidate molecular interactions. Likewise, it has also been applied to petroleum systems and, in particular, asphaltene association by concentration effects. It is also a common method for online measurements of oil in water in the offshore oil and gas industry. As a result of the complexity of crude oils and asphaltenes, many assumptions and corrections are necessary in an adequate analysis, especially of concentration effects. Unfortunately, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The spectra will still be affected by both inner filter effects and energy transfer especially important in multicomponent systems. 14 Similar to the excitation spectra in Figure 3, the SFS intensities increase with increasing isopropanol content. However, it is observed that there is a significant apparent redistribution of contributions to the spectrum while the source of fluorophores is the same, which can be due to changes to the polarity of both water phase and oil phase and redistribution of the partitioning between the two resulting phases.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…The spectra will still be affected by both inner filter effects and energy transfer especially important in multicomponent systems. 14 Similar to the excitation spectra in Figure 3, the SFS intensities increase with increasing isopropanol content. However, it is observed that there is a significant apparent redistribution of contributions to the spectrum while the source of fluorophores is the same, which can be due to changes to the polarity of both water phase and oil phase and redistribution of the partitioning between the two resulting phases.…”
Section: Resultssupporting
confidence: 60%
“…In very complex mixtures as crude oil, the variability among molecular structures is large, but substitution to pure PAHs normally only leads to displacement of the spectrum by 10 to 20 nm. The spectra will still be affected by both inner filter effects and energy transfer especially important in multicomponent systems …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…39 The importance of understanding limitations of each physical technique and assumptions in data interpretation is demonstrated by an original article by Prof. Andersen from the Technical University of Denmark, highlighting the importance of spectral correction in the fluorescence spectroscopic analysis of crude oils and asphaltenes. 40 These experimental studies are followed by two theoretical studies. Virtual experiments on real asphaltene molecules from non-contact atomic force microscopy (nc-AFM) were conducted by Prof. Janesko of Texas Christian University and Prof. Brothers of Texas A&M University at Qatar to predict bulk properties and confirm hypotheses.…”
Section: Sciencementioning
confidence: 99%
“…New insights into the asphaltene structure and aggregations were obtained by Prof. Goual at the University of Wyoming using high-resolution electron microscopy . The importance of understanding limitations of each physical technique and assumptions in data interpretation is demonstrated by an original article by Prof. Andersen from the Technical University of Denmark, highlighting the importance of spectral correction in the fluorescence spectroscopic analysis of crude oils and asphaltenes . These experimental studies are followed by two theoretical studies.…”
Section: Fundamental Research On Asphaltene Sciencementioning
confidence: 99%